Carbon-Deficient Titanium Carbide With Highly Enhanced Hardness - Li, Hui; Ma, Shuailing; Chen, Lixue; Yu, Zhuo (Frontiers in Physics, 2020)
We report the synthesis of a polycrystalline specimen of TiC1−x under high-pressure and high-temperature (HPHT) conditions. The carbon vacancy, crystal structure, Vicker hardness, elastic constants, and bond features of the synthesized specimen were investigated. Though the specimens were synthesized with stoichiometric ratio at high pressure, a robust carbon vacancy was observed using energy dispersive and X-ray photoelectron spectrum. TiC1−x exhibits almost the highest asymptotic Vickers hardness in transition-metal light-element (TMLE) compounds. In this study, using Vickers hardness characterization, the asymptotic hardness was found to be 27.1 GPa. This exceeds the hardness of most transition metal borides with high boron concentrations. Based on the first-principles calculation of the Mulliken population of Ti-C bonds, the intrinsic high Vickers hardness of TiC1−x is attributed to the combination of covalent Ti-C bonds and the optimized eight-valence-electron structure, while the extrinsic contribution comes from the harden effect of carbon defects. This work demonstrates that a higher concentration of light elements or a higher-dimensional light element framework is not the critical factor for higher hardness, and carbon vacancy is another way to strengthen the crystal structure.